Nicotinamide Riboside Vitamin B3 Mitigated C26 Adenocarcinoma-Induced Cancer Cachexia - Jong Min Park; Young Min Han; Ho Jae Lee; Yong Jin Park; Ki Baik Hahm; Ki Baik Hahm (Frontiers Media S.A., 2021)
Nicotinamide riboside (NR), vitamin B3, is a substrate for nicotinamide adenine dinucleotide (NAD+)-consuming enzymes and is a coenzyme for hydride-transfer enzymes, including adenosine diphosphate (ADP)-ribose transferases, poly (ADP-ribose) polymerases, cADP-ribose synthases, and sirtuins, which play a central role in the aging process, neurodegenerative processes, and myopathy. Since cancer cachexia is a disease condition presenting with weight loss, skeletal muscle atrophy, and loss of adipose tissue in patients with advanced cancer, we hypothesized that NR intake could ameliorate sarcopenia. In this study, we investigated whether preemptive administration of NR ameliorated C26 adenocarcinoma-induced cancer cachexia and explored anti-cachexic mechanisms focused on the changes in muscle atrophy, cachexic inflammation, and catabolic catastrophe. Dietary intake of the NR-containing pellet diet significantly attenuated cancer cachexia in a mouse model. Starting with significant inhibition of cachexic factors, tumor necrosis factor alpha, and interleukin-6, NR significantly inhibited muscle-specific ubiquitin-proteasome ligases, such as atrogin-1, muscle RING-finger protein-1 (MuRF-1), mitofusin-2, and peroxisome proliferator-activated receptor gamma coactivator-1-alpha (PCG-1α). Significant inhibition of epididymal fat lipolysis was noted with significant inhibition of adipose triglyceride lipase (ATGL) gene. Furthermore, NR administration significantly increased the levels of crucial enzymes involved in the biosynthesis of NAD+ and nicotinamide phosphoribosyl transferase and significantly inhibited the NAD+-sensitive deacetylase sirtuin 1 (SIRT1). Preemptive intake of NR in patients vulnerable to cachexia can be a preemptive option to ameliorate cancer cachexia.